2018
DOI: 10.3390/molecules23010097
|View full text |Cite
|
Sign up to set email alerts
|

Pichia cactophila and Kluyveromyces lactis are Highly Efficient Microbial Cell Factories of Natural Amino Acid-Derived Aroma Compounds

Abstract: The pivotal role of non-conventional yeast (NCY) species in formation of valuable aroma compounds in various food commodities is widely acknowledged. This fact inspires endeavors aiming at exploitation of food-derived NCYs as biocatalysts in natural aromas production. In this study, we isolated, characterized and evaluated aroma-producing capacity of two NCY representatives—Pichia cactophila 7.20 and Klyuveromyces lactis 6.10 strains. The strains were isolated from food-related habitats—goat-milk regional chee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As a result, enzymes encoded by this gene have been created and are actively involved in the production of ethyl acetate and isoamyl acetate in this yeast [Manda et al, 2017;Naresh Kumar et al, 2018]. On J Mol Microbiol Biotechnol 2019;29:1-9 DOI: 10.1159/000507551 the other hand, the enzymes encoded by the EHT1 and EAT1 genes participate in the synthesis of aromas such as ethyl ethanoate, ethyl hexanoate, and ethyl decanoate, among others [Celińska et al, 2018;Löbs et al, 2017]. Although these last two genes have been found in the putative manner, this study has also found metabolic activity has also occurred in the yeast genome, and it has been said that it is very likely that these genes have stopped being putative in some later studies.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, enzymes encoded by this gene have been created and are actively involved in the production of ethyl acetate and isoamyl acetate in this yeast [Manda et al, 2017;Naresh Kumar et al, 2018]. On J Mol Microbiol Biotechnol 2019;29:1-9 DOI: 10.1159/000507551 the other hand, the enzymes encoded by the EHT1 and EAT1 genes participate in the synthesis of aromas such as ethyl ethanoate, ethyl hexanoate, and ethyl decanoate, among others [Celińska et al, 2018;Löbs et al, 2017]. Although these last two genes have been found in the putative manner, this study has also found metabolic activity has also occurred in the yeast genome, and it has been said that it is very likely that these genes have stopped being putative in some later studies.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the total FAA contents in the PfC were the lowest among the assayed cheeses (2.70 g /100 g ). FAAs play an important role in the formation of cheese flavor, like P. cactophila and K. lactis were helpful to the production of 2-phenylethanol and isoamyl alcohol ( Celinska et al, 2018 ). These results indicate that the addition of K. marxianus A2, which had the highest protease activity, resulted in significantly higher FAA contents than those observed in the other cheeses.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, they are preferred by customers and markets and of high value. Over the decades, constant efforts have been made to produce natural aroma compounds including methionol by microbial fermentation and enzymatic catalysis. , …”
Section: Introductionmentioning
confidence: 99%